COMPARISON OF LAPAROSCOPY AND ROBOTIC SURGERY IN CHOLECYSTITIS – LITERATURE REVIEW - Mateusz Jasiński; Michał Szalach; Aleksandra Wilczyńska-Zgoda; Wojciech Suchodolski; Bartosz Burda; Małgorzata Kuczek; Aleksandra Marzec; Jakub Rusek; Błażej Madras; Mikołaj Widz (International Journal of Innovative Technologies in Social Science, 2025)
One of the most common diseases in general surgery remains cholecystitis. This is related to the prevalence of gallstones, which affects 10 to 15% of the general population. There are various types of treatment like conservative and surgical treatments, with a distinction between laparoscopic and robotic techniques. Numerous studies have been conducted which prove that laparoscopy is a safe method that significantly reduces the time of convalescence and recovery after surgery. The lack of a clear assessment of the effectiveness of treatment techniques is presented in the following paper. Advances in medicine have led to the widespread use of robotic arms in surgery, which has resulted in shorter hospital stays due to faster recovery times after surgery. This is related, among other things, to increased precision when operating instruments, and thus reduced trauma to the tissues in the abdominal cavity compared to laparoscopic surgery. However, robotic surgery has certain limitations related to the availability of equipment in specific hospitals and, above all, the increased costs of surgery compared to the use of a laparoscope. When analyzing the collected material on gallbladder surgery and possible treatment techniques for this pathology, it is not possible to clearly determine which treatment technique should be used as the gold standard in treating patients. However, it is important to remember that complications may occur in both cases, resulting in conversion to open surgery.